Much Ado about Harry: Harry Potter and the Creation of a Moral Panic - Soulliere, Danielle M. (Journal of religion and popular culture, 2010)
The unrivaled publishing success and popularity of J.K. Rowling's Harry Potter series has undoubtedly made it the popular culture phenomenon of the decade. But such popularity and success have also come with considerable controversy. The purpose of this paper is to examine the "moral panic" surrounding the book series, using Cohen's classic model, and to explore the role of the Christian Right as moral entrepreneurs in generating the "Potter Panic" through various claims-making efforts and tactics. Analyses of popular discourse concerning the Harry Potter series reveal evidence of a moral panic that has spanned nearly a decade, with geographic and temporal intensity. It is argued that the Potter Panic was not full-blown, due mostly to division among Christians, and that the panic's main legacy has been to incite debate within the larger Christian community.